Experimental Research on the Properties and Formulation of Fly Ash Based Geopolymer Grouting Material - Qingwei Zeng; Peiwei Gao; Kuan Li; Guoqing Dong; Guanglai Jin; Xuewei Sun; Jingwei Zhao; Lifeng Chen (Buildings, 2022)
This paper experimentally investigated the effects of varying contents of Na2O in a modified sodium silicate, sodium silicate moduli (Ms), and contents of granulated blast furnace slag (GBFS) on the compressive strength and drying shrinkage of fly ash (FA)-based geopolymer grouting materials at different ages. X-ray diffraction (XRD), mercury intrusion porosimetry (MIP), and scanning electron microscopy–energy dispersive X-ray spectroscopy (SEM–EDS) were used to study the influences of different amounts of GBFS on the microstructure and product compositions of FA-based geopolymer grouting materials. The results show that the content of Na2O in modified sodium silicate, Ms, and the content of GBFS play a significant role in compressive strength and drying shrinkage of FA-based geopolymer grouting materials. In addition, the influence of Ms as well as the content of GBFS on the compressive strength and drying shrinkage of FA-based geopolymer grouting materials was deeply affected by curing age. The micro-performance tests and analysis clearly showed that incorporating 30 wt% GBFS can decrease the proportion of pores with large pore sizes, improve pore size distribution, and enhance the solubility of FA and further promote the formation of C-A-S-H gel within FA-based geopolymer grouting materials.